Transcriptional regulation of plasminogen activator inhibitor-1 expression by insulin-like growth factor-1 via MAP kinases and hypoxia-inducible factor-1 in HepG2 cells - Dimova, Elitsa Y.; Möller, Ulrike; Herzig, Stephan; Fink, Trine; Zachar, Vladimir; Ebbesen, Peter; Kietzmann, Thomas (Thrombosis and Haemostasis, 2005)
Insulin-like growth factor 1 (IGF-1) and plasminogen activator inhibitor-1 (PAI-1) appear to play a crucial role in a number of processes associated with growth and tissue remodelling. IGF-1 was shown to enhance PAI-1 expression in primary hepatocytes and HepG2 hepatoma cells, but the molecular mechanisms underlying this effect have not been fully elucidated. In this study, we investigated the transcriptional mechanism and the signaling pathway by which IGF-1 mediates induction of PAI-1 expression in HepG2 cells. By using human PAI-1 promoter reporter gene assays we found that mutation of the hypoxia responsive element (HRE), which could bind hypoxia-inducible factor-1 (HIF-1), nearly abolished the induction by IGF-1. We found that IGF-1-induced up-regulation of PAI-1 expression was associated with activation of HIF-1α. Furthermore, IGF-1 enhanced HIF-1α protein levels and HIF-1 DNA-binding to each HRE, E4 and E5 as shown by EMSA. Mutation of the E-boxes, E4 and E5, did not affect the IGF-1-dependent induction of PAI-1 promoter constructs under normoxia but abolished the effect of IGF-1 under hypoxia. Inhibition of either the PI3K by LY294002 or ERK1/2 by U0126 reduced HIF-1α protein levels while both inhibitors together completely abolished the IGF-1 effect on HIF-1α. Remarkably, transfection of HepG2 cells with vectors expressing a dominant-negative PDK1 or the PKB inhibitor, TRB3, did not influence while dominant-negative Raf inhibited the IGF-1 effect on HIF-1α. Thus, IGF-1 activates human PAI-1 gene expression through activation of the PI3-kinase and ERK1/2 via HIF-1α.
Keywords: Plasminogen activator inhibitor-1; insulin-like growth factor; hypoxia-inducible factor-1; phosphatidylinositol-dependent kinase-1; extracellular regulated kinase